Patogenicidade de biofilmes mistos de candida albicans e streptococcus oralis em modelo murino submetido ao diabetes aloxânico e à terapia com fluconazol - Brito, Arella Cristina Muniz (2023)
Diabetes mellitus and oral candidiasis are diseases that have a high prevalence. Diabetic individuals may have higher rates of fungal colonization and invasion due to their systemic conditions. However, the extent to which this interrelationship can be harmful to the host remains a topic of scientific relevance. The effect of diabetes mellitus induced by alloxan and treatment with fluconazole on the virulence and pathogenicity of co-infection of mixed biofilms of Candida albicans and Streptococcus oralis in an animal model was evaluated. Male Wistar rats (n=24) were distributed into: non-diabetic and untreated group (CTR, n=6), nondiabetic and fluconazole-treated group (FLU, n=6), diabetic and untreated group (DCTR , n=6), diabetic group treated with fluconazole (DFLU, n=6). The diabetic groups received doses of 120 to 240 mg/kg of alloxan before the coinfection period. Hyperglycemia was confirmed from 250 mg/dL fasting glucose. The coinfection protocol followed with doses of prednisolone 100 mg/kg and suspensions of C. albicans ATCC 90028 and S. oralis ATCC 35037 inoculated via swab into the oral cavity and administered ad libitum in water. Animals treated with fluconazole received a dose of 10 mg/kg every 12 hours. The control groups received administration of 0.9% saline solution. At the end of the experimental period, all animals were euthanized and observed macroscopically for the presence or absence of lesions on the tongue and microscopically using histochemical methods of Hematoxylin-eosin (HE) and Periodic Acid-Schiff (PAS) to evaluate changes in the palate, tongue and pancreas. The extraction and quantification of C. albicans DNA from the tongue was also carried out, as well as gene expression for SAP6 and HWP1 using Real-time RT-qPCR. Data were analyzed by one-way ANOVA and Tukey test (α= 5%). Lesions were observed on the tongues of animals in the DCTR group. The groups presented erythematous areas on the surface. In histological sections, the DCTR group showed more changes in relation to the other groups, with emphasis on epithelial invasion by hyphae and hyperkeratosis on the tongue, as well as epithelial reduction and the presence of an ulcer with dilated vessels on the palate. All diabetic animals showed destruction of β cells in the Islets of Langerhans. The relative quantification of C. albicans DNA in the animals' tongues indicated that there was a difference between the DCTR group (3.45±0.93) and the others (p<0.05). In the rest of the groups there were no differences (p>0.05). SAP6 gene expression xii i ranged from 1.00±0.29 in the non-diabetic group treated with fluconazole to 1.16±0.38 for the diabetic group not treated with fluconazole, which indicated that there was no significant difference in the groups evaluated ( p>0.05). Regarding HWP1 gene expression, it was observed that there was a difference between the groups of healthy animals and diabetic animals (p<0.05). From the results found, the diabetic groups not treated with fluconazole showed a greater number of macroscopic and histological changes, as well as greater quantification of C. albicans and gene expression for HWP1. Treatment with fluconazole was effective in reducing fungal invasion. The present research contributes to new studies that may consider alloxan diabetes and fluconazole treatment to evaluate the effects of oral candidiasis in murine models.